Investigation of the matematical model of the multimensional automatic control system with delays - Jonas Rimas (Lietuvos Matematikos Rinkinys)
The mathematical model of the mutual synchronisation system composed of n = 2p + 1  (p ∈ N) joined into a chain oscillators is investigated. The precise analytical expressions of the elements of the step responses matrix of the system are obtained.